Performance Analysis and Techno-Economic Evaluation of Solar Energy Retrofitting for Coal-Fired Power Plant in Central Kalimantan Province - Irfan Ali; Hadiyanto Hadiyanto; Asep Yoyo Wardaya (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
The power generation sector contributes to climate change. Mitigation efforts are essential to ensure that the commitment to limiting the global temperature increase below 2°C stays on course. One option is to retrofit an existing power plant with new technology that allows integration with renewable energy. This study examines the incorporation of solar energy systems into the operational processes of coal-fired power plants. Utilizing solar energy to substitute steam extraction from high-pressure feed water heater No. 7. This study analyzes the performance of the power plant before and after the retrofit scenario within both power-boost (PB) and fuel-save (FS) modes. Performances under different load conditions also investigated. The results reveal that the thermal efficiency within both FS and power-boost (PB) modes increased up to 2 % compared to the base scenario. In both power-boost and fuel-save (FS) modes, there is a notable reduction in specific fuel consumption, with power-boost mode experiencing a decrease of 15.05 g/kWh and fuel-save mode showing a decrease of 15.75 g/kWh. Thus, the decreasing coal consumption implies reduced CO2 emissions within both FS and power-boost (PB) modes by 4.69 % and 4,94 %, respectively. Results under different loads show that the solar percentage and the rise in solar-to-electricity efficiency with decreasing loads. When operated in fuel-save (FS) mode, the proportions of solar electricity at VWO, 100%, 75%, and 50% load rates are 5.23 %, 5.53 %, 7.76%, and 11.92%, respectively. Moreover, the LCOE for solar electricity for both modes is 0.0267 USD/kWh, with expected investment returns of 5.87 years.